Influence of the autonomic nervous system on circadian patterns of myocardial ischaemia: comparison of stable angina with the early postinfarction period. Issue 4 (April 1994) - Marchant, B.; Stevenson, R.; Vaishnav, S.; Wilkinson, P.; Ranjadayalan, K.; Timmis, A. D.
Abstract : OBJECTIVE--To compare the circadian rhythm of myocardial ischaemia in patients with stable angina with that in patients in the early postinfarction period with particular emphasis on the role of the autonomic nervous system. PATIENTS--44 patients with stable angina and ischaemia on treadmill testing (group A) were compared with 131 patients in the early postinfarction period (group B). All had 48 hour ambulatory Holter monitoring. SETTING--Coronary care unit and cardiology department of a district general hospital. DESIGN--Prospective, between group, comparative study. RESULTS--337 ischaemic episodes occurred in 35 patients in group A and 370 ischaemic episodes occurred in 65 patients in group B. 34% of patients in group A had only silent episodes of ischaemia compared with 97% in group B (p < 0.0001). In group A ischaemic episodes showed a circadian rhythm that peaked during the daytime hours (p < 0.0001), but this was not seen in group B. Both the high (0.15-0.40 Hz) and low (0.04-0.15 Hz) frequency spectral components of heart rate variability showed a clear circadian rhythm (p < 0.0001); peak values occurred during the sleeping hours, although this pattern was less pronounced in group B. The ratio of low to high frequency variability (a measure of sympathovagal balance) showed a peak in daytime hours in group A (p < 0.002), but this was not seen in group B. CONCLUSION--In stable angina, myocardial ischaemia peaks during the day and is associated with a similar circadian rhythm of sympathovagal balance. In the early postinfarction period both the ischaemic and sympathovagal rhythms are severely diminished or lost altogether. Circadian changes in sympathovagal tone may explain, at least in part, the circadian rhythm of ambulatory myocardial ischaemia in patients with stable angina.